Advocacy : championing ideas and influencing others - Daly, John A. (John Augustine), 1952- (Yale University Press, 2011)
When a group of people gather together to generate ideas for solving a problem or achieving a goal, sometimes the best ideas are passed over. Worse, a problematic suggestion with far less likelihood of success may be selected instead. Why would a group dismiss an option that would be more effective? The author, a leadership and communications expert, has an answer: it wasn't sold to them well. If the best idea is yours, how can you increase the chances that it gains the support of the group? In this book, the author explains in full detail how to transform ideas into practice. To be successful, leaders in every type of organization must find practical and action-oriented ways to market their ideas and achieve buy-in from the members of the group. He offers a comprehensive action guide that explains how to shape opinion, inspire action, and achieve results. Drawing on current research in the fields of persuasion, power relations, and behavior change, he discusses the complex factors involved in selling an idea, the context of the communication, the type of message being promoted, the nature and interests of the audience, the emotional tenor of the issues at stake, and much more. This book works as a guide for the businessperson, politician, or any other member of a group who seeks the satisfaction of having his or her own idea take shape and become reality